Friendly Environment in Gurukul and Psychologically Motivation of Students towards Gurukul Education - Adhikari, Toya Nath (Interdisciplinary Research in Education, 2023)
The goal of this study is to look at the psychological components of Gurukul students' motivation for education. The psychological component of persons is concerned with their mind and thoughts. The psychological component of Gurukul students relates to their feelings, attitudes, understanding, and conduct in connection to the Gurukul environment as a whole. The psychosocial component of students entails the interaction between students' intrapersonal psychological aspects and the entire Gurukul setting. A psychological aspect is frequently defined as a student's psychological growth in relation to their academic environment. The methodology of this study is qualitative. The researcher collected data for this work through interviews and focus group discussions. The interview is utilized for teachers, while the focus group discussion is used for students. The sampling is purposive and teachers and students are selected purposively who are pursuing education in gurukuls. The findings of this study show that the students are self-motivated to study in gurukuls. And the conclusion of this article is that the appeal of Gurukul is growing day by day, and many pupils are drawn to the Gurukul education system.